2018
DOI: 10.1007/978-981-13-1214-4
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Constituents in Soil

Abstract: distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license and indicate if changes were made. The images or other third party material in this book are included in the book's Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the book's Creative Commons license and your intended use is not permitted by statutory regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Based on that result, Sueto and Nakaishi (1992) reported that this commercial product is typically pure montmorillonite and confirmed the chemical composition of this clay supplied by the company (Kunimine Co., Ltd.). The purity of the same product was also reported by Nanzyo and Kanno (2018). 2) The dispersion saturated with NaCl was rinsed using the dialysis process with distilled water repeatedly.…”
Section: Montmorillonite Suspension Preparationmentioning
confidence: 97%
“…Based on that result, Sueto and Nakaishi (1992) reported that this commercial product is typically pure montmorillonite and confirmed the chemical composition of this clay supplied by the company (Kunimine Co., Ltd.). The purity of the same product was also reported by Nanzyo and Kanno (2018). 2) The dispersion saturated with NaCl was rinsed using the dialysis process with distilled water repeatedly.…”
Section: Montmorillonite Suspension Preparationmentioning
confidence: 97%
“…They are mainly silicate minerals with varied bonding structure [28]. Other common primary minerals in soils include oxides/hydroxides of titanium/iron/manganese, carbonates, as well as non-crystalline inorganic materials such as volcanic glasses [29]. Primary minerals undergo various physical, chemical, biochemical and human-induced weathering in soils.…”
Section: The Role Of Soils In Enhanced Weatheringmentioning
confidence: 99%
“…Isomorphous substitution is the substitution of a cation within the tetrahedral and octahedral layer lattice clay by a cation of lower-valent or lower charge having similar size (within permissible limit) leads to the development of permanent charge [20]. Examples are the permanent negative charge developed in the layer lattice clay structure of mica, vermiculite, illite, etc.…”
Section: Origin Of Chargementioning
confidence: 99%